ANALISIS HASIL BELAJAR SISWA BERORIENTASI HOTS PADA PEMBELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR - Valentino Yusia Helpi; Imanuel Sairo Awang; Muhammad Rian Subekti (STKIP Persada Khatulistiwa Sintang, 2022)
This study is motivated by student learning outcomes oriented to Higher Order Thinking Skills (HOTS) in Mathematics Learning in grade IV SDN 11 Nanga Lemetak in the 2021/2022 academic year. This study describes student learning outcomes oriented to Higher Order Thinking Skills (HOTS), the factors that influence student learning outcomes oriented to Higher Order Thinking Skills (HOTS). The study approach used is a qualitative phenomenological approach. This study's data collection techniques were unstructured observation techniques, semi-structured interview techniques, and documentation techniques. Based on the study results, the average HOTS thinking ability in mathematics subjects in grade IV SDN 11 Nanga Lemetak was 58.73% in the good category. The indicator (Comparing) is 84.76% in the high category (High), the indicator (Interpreting) is 49.52% in the low category (Low), and the indicator (Making) 41.90% is categorized as low (Low).